2004
DOI: 10.1111/j.1742-7843.2004.pto940607.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Polysaccharide from Eleutherococcus senticosus Stems Attenuates Fulminant Hepatic Failure Induced by D‐Galactosamine and Lipopolysaccharide in Mice

Abstract: The aim of this study was to investigate whether Eleutherococcus senticosus stems could attenuate D-galactosamine/lipopolysaccharide-induced fulminant hepatic failure in mice. E. senticosus, known as Siberian ginseng, is a popular folk medicine used as a tonic in Asia. Preparations of E. senticosus used in this study were as follows; (i) 70% ethanol extract (ii) water extract (iii) ethanol-soluble part of the water extract (iv) polysaccharide obtained as an 80% ethanol insoluble of the water extract. Preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Hence, they strongly inhibited the generation of nitric oxide in lipopolysaccharide-stimulated RAW murine macrophage. In addition, these results are in agreement with the results of Park et al90 who found that water-soluble polysaccharide from Eleutherococcus senticosus reduced the NO and lipid peroxidation levels in serum of mice. In the present study, polysaccharides extracted from the green alga, U. lactuca , profoundly decreased the serum NO level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, they strongly inhibited the generation of nitric oxide in lipopolysaccharide-stimulated RAW murine macrophage. In addition, these results are in agreement with the results of Park et al90 who found that water-soluble polysaccharide from Eleutherococcus senticosus reduced the NO and lipid peroxidation levels in serum of mice. In the present study, polysaccharides extracted from the green alga, U. lactuca , profoundly decreased the serum NO level.…”
Section: Discussionsupporting
confidence: 93%
“…Water-soluble polysaccharide from E. senticosus increased the activities of CAT and GPx in kidney90 and attenuated the renal dysfunction 104. The increase in antioxidant enzymes by U. lactuca polysaccharides suggests that it inhibits the process of oxidative stress-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, recent studies demonstrating that extracts derived from Acanthopanax senticosus (AS), a well-known herb widely distributing in northern regions of Korea, Japan, and China (Deyama et al, 2001; Park et al, 2004), improved immune responses (Kong et al, 2007a), enhanced utilization efficiency of nutrition (Kong et al, 2009a), and modulated gut health of weaned piglets (Yin et al, 2008; Fang et al, 2009) have gained extensive attention. Above all, Acanthopanax senticosus polysaccharide (ASPS) as a extract typically concentrated in the root of AS, in human and rodents, has been shown to have potent immunomodulatory activity in vitro and in vivo by improving lymphocyte proliferation (Chen et al, 2011), inducing cytokine actions of interleukin-1beta (IL-1β) and interleukin-6 (IL-6) (Steinmann et al, 2001), enhancing activities of B cells and phagocytosis of macrophages (Han et al, 2003), inhibiting the transferred tumor growths and ameliorating toxicities of toxic substances by immunomodulatory role of ASPS (Shen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Acanthopanax senticosus is a well‐recognised herbal plant and widely used in the Northeastern regions of China, Korea, Japan, and Russia (Davydov & Krikorian, ; Park et al, ) and other parts of the world. It is mainly composed of EB and Eleutheroside E (Takeshi, Sansei, & Yoshihisa, ).…”
Section: Introductionmentioning
confidence: 99%